Academic Motivation, Cyberloafing, and Multiscreen Addiction in University Students - Nurullah Çakmak; Şahin Gökçearslan (Uluslararası Türk Eğitim Bilimleri Dergisi)
The problem of academic motivation, cyberloafing, and multiple screen addiction has recently gained importance and has come to the forefront of research. This study aims to fill the research gap in the literature by examining the relationships between these variables. In the study, the variables were analyzed in terms of gender, grade level, and daily screen usage habits. Quantitative and cross-sectional research design was used in the study, and data were collected from 337 university students through a questionnaire. According to the findings of the study, no significant relationship was found between academic motivation and cyberloafing. A positive and significant relationship was found between multiple screen addiction and cyberloafing. Female students have a higher risk of multiple screen addiction compared to male students. As the grade level increases, the tendency to cyberloaf decreases. It was found that as the level of education increases, less cyberloafing is practiced. As daily screen time increases, cyberloafing and multiscreen addiction also increase. The results suggest that reducing digital distractions and motivational strategies in educational processes can be effective in reducing cyberloafing tendency. In addition, it emphasizes the importance of improving students' time management skills in their use of digital devices.